Sustainable Transformation of Dairy Farmers in Latin America: A Perspective from Agribusiness - Pacheco-Hernández, Armando; Ramírez-Umaña, Mauricio Vladimir; Bonilla-Landaverry, Gesly Aníbal; García-López, Roberto de Jesús (Asian Journal of Science, Technology, Engineering, and Art, 2025)
This study reports on an intervention conducted in a Cuban dairy farm with structural and technological conditions representative of national production systems, aiming to identify and address key constraints limiting sustainable productivity. The initial diagnosis revealed deficiencies in replacement heifer quality, degraded grazing pastures, and low reproductive efficiency. In response, a four-year strategic transformation plan was implemented, focusing on enhancing productive efficiency and business profitability. The herd comprised predominantly crossbred Holstein cows, with some purebred Holsteins selected for their high milk yield potential. Results demonstrated a marked improvement in performance, with milk yield per hectare increasing from 2,720 to 5,353 liters and reproductive success rising from 70% to 85%. These gains were accompanied by a significant reduction in production costs, achieved through optimized pasture use and reduced dependence on external feed supplements. The intervention transformed the farm into an efficient agribusiness model, characterized by rational input use, sustainable pasture intensification, and genetic and reproductive improvements. Overall, the case study underscores the feasibility of achieving high milk yields under low-input tropical systems by integrating sustainability, productivity, and profitability, offering a replicable model for strengthening the dairy sector in similar environments.